Aplikasi Akuntansi dan Excel dalam Menunjang Pelaporan Keuangan pada UMKM Mitra Binaan DEFEND ID Bandung - Sendi Gusnandar Arnan; Muhammad Ali; Syafrizal Ikram; Suryana Suryana (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The role of MSMEs is very important for the Indonesian economy, namely contributing to Indonesia's Gross Domestic Product (GDP). National MSMEs have also been officially registered in the state gazette, in line with the government's decision to establish Law number 20 of 2008 (Law 20/2008) concerning Micro, Small, and Medium Enterprises. According to the aforementioned Law, MSMEs is a term used for businesses run by individuals, households, or small-sized business entities. The continued ineffectiveness of MSME financial management related to financial management accountability is a problem currently being faced by MSMEs. In addition, there is still a lack of knowledge and understanding of Excel and accounting applications, especially regarding financial administration and reporting in MSMEs. Therefore, we as a community service team strive with technical guidance, training and workshops on Excel and Accounting will be able to improve the knowledge and understanding and skills of MSME managers in making financial reports that comply with accounting standards. This Community Service Activity was carried out for micro, small, and medium enterprises (MSMEs) fostered by DEFEND ID in Bandung City. This Community Service program aims to improve skills and understanding of Excel applications, accounting, and financial management, reporting, and accountability for MSMEs.